Responding to Religious Claims in a Secular Democracy: The Turkish Case - (:unkn) unknown (SETA FOUNDATION, 2015)
This article examines state responses to claims made by religious groups, unorthodox communities and minority religions in Turkey and argues that paradigmatic changes have taken place, especially under the Justice and Development Party (AK Party) governments since 2002. Under the AK Party governments, the conventional meaning attached to secularism gradually changed from a restrictive one to a relatively inclusive and libertarian one, as evidenced by the lifting of the headscarf ban in the public sphere. Currently, responding to the claims of unorthodox and non-Muslim communities has become part of the social fabric of Turkey, although room for improvement remains.